Selected aspects of venous ulcers conservative treatment. Part II: Wound cleansing - Szewczyk, Maria T.; Jawień, Arkadiusz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
Venous ulcers are the most often complication of chronic venous disease. Topical treatment is one of many components of effective and accurate therapy. Pathogenesis, in which the main role plays venous hypertension, requires at first elimination or reduction of causative factors. The gold standard of conservative treatment of venous ulcers is compression therapy followed by wound cleansing and active moist dressings. Localization, depth, amount of exudate and general state of patient are all determinants of the way of necrotic tissues elimination. Wounds are usually cleaned with variety of conservative methods: mechanical, enzymatic, active dressings increasing the moist environment and autholytic debridement. Superficial necrotic tissues can be surgically debridet only in special and justified situations. The aim of the study was to present the methods of wound cleansing and proceeding during the infection. Moreover the principles of active dresings use were discussed.